EVALUATION OF IT SERVICE MANAGEMENT IMPLEMENTATION RELATED TO INCIDENT MANAGEMENT WITH ITIL FRAMEWORK IN PT.XYZ - Oktiviana, Liana; Jayadi, Riyanto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Information Technology Service Management (ITSM) plays an important role for companies to be able to plan IT Service Management, especially in the implementation of Incident Management and Service Level Management (SLM). This study will discuss the evaluation of the maturity of the service operation domain in the management of information technology services belonging to PT.XYZ. The goal of this study is to measure and determine the maturity level of PT. XYZ related to incident management service in order to find out recommendations for the improvement of IT service management operations. The following procedures were to analyze the interpretation of the existing and the company condition, and provide recommendation lists of the corrective actions to overcome weaknesses and to create improvements in IT Service. Then the recommendations are formulated and refer to several processes that are not yet optimal. It is necessary to evaluate the measurement and recording of existing performance and services so that it can describe the performance that needs to be improved, reduced or eliminated if it is felt to be an obstacle to the progress of the PT. XYZ services related to the incident management.